Determinación del material particulado total producido por la extracción y trituración del material pétreo con la finalidad de elaborar una propuesta de plan de manejo en el área minera Kumochi sector Las Viñas parroquia Izamba, cantón Ambato. período 2014 - Medina Ayala, Marco Fabián (2014)
The extracion and crushing of stone material in La Mina Ambato, Nieto and Kumochi Uno, canteras they located in Ambato City, Las Viñas in mining Area Kumochi within the production process is generated of particulate Material Total which influences the health of workers and the quality of environmental factors in the direct influence area, wáter and air through the perfomance of various methods especially quantitative it determinated amount of PM Total with there monitoring for 24 hours at critical points in the extraction and crushing of stone material, it obtained though analysis of direction and speed wind, results with analyzes of atmospheric stability it allowed models of digital dispersion stone material with levels at different distances from the emission source locating the results outside the rule at less tan 100 meters from the reception area of distances....